"Exchange lost" in leader–member exchange theory and research: A critique and a reconceptualization. (May 2015) - Sheer, Vivian C
Several problems have persisted in the voluminous body of leader–member exchange (LMX) literature. The most salient problem is the absence of an explicit conceptual definition of LMX in earlier theoretical works and later research. In general, LMX is treated as attributes of the leader and the leader–member relationship rather than interaction-based exchange behavior. The lack of clarity in conceptual definition has led to LMX instruments that measure a hodgepodge of leader and relationship attributes other than LMX. Consequently, findings gleaned with different LMX measures cannot be synthesized meaningfully. This essay introduces a reconceptualization of LMX as a behavior-based construct that consists of four exchange aspects: tangible work, tangible social, work communication, and social communication. A systematic approach to creating a valid measure (LMX-Behavior) is proposed for future research.